TEMA-CLINICAL USEFULNESS OF A NEW EQUATION FOR ESTIMATING BODY FAT - Ro'ziqulova Gulhayo Sharofutdinovna (Western European Studies, 2025)
Accurate estimation of body fat is essential in both clinical and research settings for assessing obesity-related health risks. Traditional methods such as BMI, skinfold measurements, and bioelectrical impedance have limitations. This article presents and evaluates a newly proposed equation for estimating body fat percentage based on readily available anthropometric data. The clinical utility of this new model is compared with existing methods in terms of accuracy, accessibility, and applicability in different population groups.
Keywords: dy fat estimation; body composition